2007
DOI: 10.2307/30035561
|View full text |Cite
|
Sign up to set email alerts
|

Use of Evidence-Based, Small-Group Reading Instruction for English Language Learners in Elementary Grades: Secondary-Tier Intervention

Abstract: This experimental/comparison study of secondary-level, small-group instruction included 318 first- and second-grade students (170 ELL and 148 English-only) from six elementary schools. All schools served high numbers of ELL students with varying school SES in urban and suburban communities. Experimental schools implemented a three-tier model of intervention. In addition to primary-tier reading instruction, the second-tier, small-group experimental interventions included use of (a) evidence-based direct instruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 20 publications
0
41
0
2
Order By: Relevance
“…Six studies assessed reading fluency (Calhoon, Al Otaiba, Cihak, King, & Avalos, 2007;Denton, Wexler, Vaughn, & Bryan, 2008;Gunn, Smolkowski, Biglan, Black, & Blair, 2005;Kamps et al, 2007;McMaster, Kung, Han, & Cao, 2008;Sáenz, Fuchs, & Fuchs, 2005). Rather than focusing solely on fluency, usually these studies examined fluency in the context of more comprehensive reading programs that also focused on phonological awareness, phonics, and/or comprehension.…”
Section: Updatementioning
confidence: 99%
See 1 more Smart Citation
“…Six studies assessed reading fluency (Calhoon, Al Otaiba, Cihak, King, & Avalos, 2007;Denton, Wexler, Vaughn, & Bryan, 2008;Gunn, Smolkowski, Biglan, Black, & Blair, 2005;Kamps et al, 2007;McMaster, Kung, Han, & Cao, 2008;Sáenz, Fuchs, & Fuchs, 2005). Rather than focusing solely on fluency, usually these studies examined fluency in the context of more comprehensive reading programs that also focused on phonological awareness, phonics, and/or comprehension.…”
Section: Updatementioning
confidence: 99%
“…Our review located 10 studies with reading comprehension outcomes (Denton et al, 2008;Ehri, Dreyr, Flugman, & Gross, 2007;Fung, Wilkinson, & Moore, 2003;Kamps et al, 2007;Liang, Peterson, & Graves, 2005;Lovett et al, 2008;Roberts & Neal, 2004;Sáenz, Fuchs, & Fuchs, 2005;Solari & Gerber, 2008;Swanson, Hodson, & Schommer-Aikins, 2005). Most studies investigated the effect of comprehensive and multi-faceted literacy programs on the comprehension of ELLs.…”
Section: Updatementioning
confidence: 99%
“…The program produced significant gains in word reading for EL first graders, but only for students with higher oral vocabulary scores. In an earlier study, Kamps et al (2007) examined the effects of direct phonics instruction in a year-long, small group intervention with first and second grade ELs and reported that intervention students showed superior oral reading fluency scores compared to ELs receiving typical classroom instruction. More recently, Begeny et al (2012) implemented a reading fluency program called Helping Early Literacy with Practice Strategies (HELPS).…”
Section: Introductionmentioning
confidence: 99%
“…Gerber and his team of researchers concluded that small-group interventions in phonological awareness in Spanish could be quite effective for K-1 English language learners. Haager and Windmueller (2001) and Kamps et al (2007) successfully implemented second-tier interventions in English for English language learners.…”
Section: Literature Reviewmentioning
confidence: 99%